Pengembangan Karakter dalam Pembelajaran Matematika: Model di Prodi Pendidikan Matematika FKIP UMS - Masduki, Masduki; Khotimah, Rita P; Sutarni, Sri; Toyib, Muhammad; Kholid, Muhammad; Santoso, Kurniawan Budi (Jurnal VARIDIKA, 2014)
This research aimed to design a strategy to develop character learning mathematics students that were based on the values of Islam. This study were in the frame of research and development method using qualitative approach. Subject of this research was the first year of undergraduate students of mathematics education department who took basic mathematics courses. Mathematics learning strategies in developing th character were designed in three stages to develop students character. The first stage was the inculcation. At this stage, lecturer facilitated students with activities that were able to raise awareness of the value of the character in learning. The second stage was Implementation where the lecturers facilitated student learning activities that fostered character value. Activities fostered values characters implicitly include group discussion, problems solving, seeking information from various sources, preparations reports, and presentations. The final stage was reflection, where the lecturer together with students did reflection on themselves and on the values of the characters that had not been well grown in learning. The results of interview with students suggest that the use of learning strategies has a positive impact on student character development.